2022
DOI: 10.3390/ijns8010018
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for and Management of Endocrine Dysfunction in Adrenoleukodystrophy

Abstract: Adrenoleukodystrophy (ALD) is a peroxisomal disorder affecting the nervous system, adrenal cortical function, and testicular function. Newborn screening for ALD has the potential to identify patients at high risk for life-threatening adrenal crisis and cerebral ALD. The current understanding of the natural history of endocrine dysfunction is limited. Surveillance guidelines for males with ALD were developed to address the unpredictable nature of evolving adrenal insufficiency. Early recognition and management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…Life-threatening adrenal crisis may occur and requires prompt treatment. 32 Mineralocorticoid function often remains intact, likely because VLCFAs accumulate to a lesser degree in the zona glomerulosa than the other regions within the adrenal cortex. 31 However, aldosterone deficiency has been observed in X-ALD and manifests with salt-craving.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Life-threatening adrenal crisis may occur and requires prompt treatment. 32 Mineralocorticoid function often remains intact, likely because VLCFAs accumulate to a lesser degree in the zona glomerulosa than the other regions within the adrenal cortex. 31 However, aldosterone deficiency has been observed in X-ALD and manifests with salt-craving.…”
Section: Dovepressmentioning
confidence: 99%
“…If untreated, it causes hyponatremia, hyperkalemia, mild metabolic acidosis, and may result in hypotension. 32 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to adrenal androgen deficiencies, primary testicular dysfunction is known to be a manifestation of disease among men with ALD. However, a recent review found sparse reports of the effects of low testosterone in ALD 90 . Potential contribution of low testosterone to cognition and mental health might be estimated from the broader literature on low testosterone, which can be associated with depression and lower scores on neurocognitive testing, including memory, processing speed, attention, visuospatial, and language skills 91–93 .…”
Section: Males With Aldmentioning
confidence: 99%
“…However, a recent review found sparse reports of the effects of low testosterone in ALD. 90 Potential contribution of low testosterone to cognition and mental health might be estimated from the broader literature on low testosterone, which can be associated with depression and lower scores on neurocognitive testing, including memory, processing speed, attention, visuospatial, and language skills. [91][92][93] However, the weight of this contribution to the neuropsychological presentation of adults with ALD is presently unclear and worth further investigation.…”
Section: Impact Of Endocrine Dysfunction On Neuropsychological Statusmentioning
confidence: 99%
“…The correct interpretation of the pathogenicity of a variant ABCD1 is especially important. The identification of an inherited gene mutation can lead to a life-changing diagnosis of ALD in members of an extended family [ 9 , 10 ]. Genetic testing of X-linked ALD and screening of neonates have helped identify novel variants of unknown significance (VUSs), highlighting the need for further genetic characterization.…”
Section: Introductionmentioning
confidence: 99%